New Baetidae (Insecta: Ephemeroptera) Records from Venezuela and Nymph Description of an Unnamed Fallceon Species - Paulo Vilela Cruz; Rafael Boldrini; Carlos F. Quinto; Hortencia Frontado (International Journal of Zoology)
The Ephemeroptera fauna in Venezuela is poorly known, as is also the case in others areas in South America. Recently, two studies increased from 33 to 50 the number of species recorded in Venezuela. The objective of the present study is to report for the first time in Venezuela the following species: Baetodes levis; Camelobaetidius edmundsi; Fallceon sp.; Mayobaetis ellenae. The nymph of Fallceon sp. is described, but is not named because adults were not reared to allow species identification; however, description of this nymph indicates the presence of this genus in South America.